2018
DOI: 10.13075/mp.5893.00688
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal, hearing and skin problems related to playing the instrument

Abstract: StreszczenieWstęp: Obciążenie fizyczne, ekspozycja na hałas oraz intensywny kontakt skóry z instrumentem muzycznym wynikające z pracy muzyka mają wpływ na rozwój dolegliwości układów mięśniowo-szkieletowego, słuchowego oraz skóry. Celem tego opracowania jest rozpoznanie problemów zdrowotnych związanych z grą na instrumencie w grupie polskich muzyków oraz wskazanie różnic w tym zakresie pomiędzy studentami a profesjonalistami. Materiał i metody: W badaniu kwestionariuszowym udział wzięło 255 muzyków, którzy odp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
(64 reference statements)
0
5
0
1
Order By: Relevance
“…Studies in this labor population try to estimate the rate of musculoskeletal disorders, bringing varied definitions and numbers 15 , and some show that there are no differences between the group of professionals and the group of students 4 . In general, these rates range from 10 to 79%, sometimes diverging when specific areas of the body are analyzed and may reach up to 94.8% when considering the symptoms reported in a period of up to one year 4,[16][17][18] . Although the types of disorders are numerous, performance-related pain is frequently addressed, being present in 18.3 to 79.7% of the musicians in the samples studied 5,19,20 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in this labor population try to estimate the rate of musculoskeletal disorders, bringing varied definitions and numbers 15 , and some show that there are no differences between the group of professionals and the group of students 4 . In general, these rates range from 10 to 79%, sometimes diverging when specific areas of the body are analyzed and may reach up to 94.8% when considering the symptoms reported in a period of up to one year 4,[16][17][18] . Although the types of disorders are numerous, performance-related pain is frequently addressed, being present in 18.3 to 79.7% of the musicians in the samples studied 5,19,20 .…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Poland points out musculoskeletal problems as highly relevant among musicians, requiring concern 4 . In Brazil, evaluating the main musculoskeletal complaints among music students and professionals in the ABC region of São Paulo, it was observed that, regardless of the type of instrument used (string, percussion, or wind instrument), the pain was a symptom mentioned by half or more of the participants, especially in the regions of the hands and dorsal and lumbar columns, and less than half of them had any medical follow-up in this regard 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the different types of musical instruments, defects and postural stability disorders may differ between musicians. Musicians playing asymmetrical instruments such as the violin or the cello seem to be particularly at risk of posture disorders [13,14]. Recent studies confirm the occurrence of musculoskeletal disorders in 80-90% of the musicians [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Τέλος, η βαρηκοΐα οδηγεί σε αύξηση των μυοσκελετικών προβλημάτων καθώς οι μουσικοί στην προσπάθεια τους να ακούσουν καλυτέρα αυξάνουν την ένταση κατά τη διάρκεια της εξάσκησής τους και ασκούν μεγαλύτερη δύναμη στα όργανα όπου αυτό είναι εφικτό. Τα ποσοστά των μουσικών με μυοσκλετικά προβλήματα είναι αρκετά υψηλά (Jacukowicz and Wężyk, 2018).…”
Section: συμπτωματολογία γενικάunclassified